2003
DOI: 10.1063/1.1605939
|View full text |Cite
|
Sign up to set email alerts
|

The hydration of the OH radical: Microsolvation modeling and statistical mechanics simulation

Abstract: The hydration of the hydroxyl OH radical has been investigated by microsolvation modeling and statistical mechanics Monte Carlo simulations. The microsolvation approach was based on density functional theory ͑DFT͒ calculations for OH-(H 2 O) 1-6 and (H 2 O) 1-7 clusters. The results from microsolvation indicate that the binding enthalpies of the OH radical and water molecule to small water clusters are similar. Monte Carlo simulations predict that the hydration enthalpy of the OH radical, ⌬ hyd H(OH,g), is Ϫ39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 63 publications
7
69
1
Order By: Relevance
“…The OH-H 2 O band at 3472.5 cm -1 is roughly 30-40 times more intense than the OH monomer band at 3566 cm -1 ( Figure 2). However, the band intensities of the corresponding parent molecules (H 2 O) 2 The lower trace of Figure 4 shows the difference IR spectrum upon VUV photolysis in the H 2 O bending region. The frequency of the observed photoproduct band is also listed in Table 2.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The OH-H 2 O band at 3472.5 cm -1 is roughly 30-40 times more intense than the OH monomer band at 3566 cm -1 ( Figure 2). However, the band intensities of the corresponding parent molecules (H 2 O) 2 The lower trace of Figure 4 shows the difference IR spectrum upon VUV photolysis in the H 2 O bending region. The frequency of the observed photoproduct band is also listed in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…IR bands due to OH-(H 2 O) n show a simple structure without any splitting due to site effects. IR bands due to the OH radical stretch and HOH bending vibrations of OH-H 2 O and OH-(H 2 O) 2 have been assigned with the aid of quantum chemical calculations. Reaction of OH-H 2 O and H to form (H 2 O) 2 observed under the dark conditions provides undisputed evidence for the spectroscopic assignments.…”
Section: Resultsmentioning
confidence: 99%
“…22 The OH-OH 2 complex also provides a starting point for understanding the hydration structures of OH in liquid water. [23][24][25] Experimentally, OH-OH 2 has been observed by infrared spectroscopy in cryogenic matrices, 4,6,7 and more recently by Fourier transform microwave spectroscopy in the gas phase. 10,11 Theoretically, it has been studied by a variety of computational methods, which have focused on energetics, structure, and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The positive values of n obtained at all the studied temperatures reflected the uptake of OHÁ when Ab bound to CS. A variation in the micropolarity of the environment surrounding some residues of CS and some side chains of certain active site residues of the Ab due to the strong role played by OHÁ radical as a proton donor in water [31] explained this uptake. Also, the Ab-CS complex was stabilized by hydrogen bonds between OHÁ radical with neighboring polar groups of Ab and/or CS.…”
Section: Resultsmentioning
confidence: 95%
“…It was demonstrated that OHÁ radical-induced alterations in the binding sites of protein molecule played an important role in the changes of ligands binding to protein [29,30]. From sequential Monte Carlo/DFT calculations, the dipole moment and the hydration enthalpy of the OHÁ radical in water were, respectively, around 2.2D and -39.1 kJ/mol [31]. Thus, OHÁ radical interacted with the surface of CS through dipole-dipole interactions and can therefore modify the rigidity of the CS structure and influence the access of the protein to the CS binding site.…”
Section: Resultsmentioning
confidence: 98%